La piedra del cielo: algunos aspectos de la educación e iniciación religiosa de los príncipes incas - Ziólkowski, Mariusz S. (1984)
In this article the author tries to determine what was the specific character of the "information" that the Sapan, Inka possessed, this quality, earned him his high position in the Inca religious and state hierarchy.